Exploring how awareness of character strengths can benefit mental health nurses. (2nd August 2019) - Macfarlane, Jan
Abstract : This is the third in a series of articles that explores the meaning of positive psychology and the importance of applying the latest research findings for the wellbeing of the mental health workforce. It will focus on character strengths as a positive psychology intervention from its development to present day use and how it is relevant to mental health nursing. The activities provided in the boxes throughout the article will help the reader identify their own strengths and understand how to further develop their transferability to daily work, home life, education and recreation.